ISSUES OF SAFETY OF LIVELIHOOD AND ENVIRONMENT IN COMBINATION WITH GEODESIC TECHNOLOGIES - Журавська, Наталія; Коваль, Вадим (SWorldJournal, 2024)
The implementation of modern geodetic technologies for the effective management of territories and resources, based on the example of self-organization of specialists in the field of geodesy, requires a comprehensive approach to solving problems of a mili